2019
DOI: 10.1186/s13550-019-0535-4
|View full text |Cite
|
Sign up to set email alerts
|

Impact of acquisition time and penalizing factor in a block-sequential regularized expectation maximization reconstruction algorithm on a Si-photomultiplier-based PET-CT system for 18F-FDG

Abstract: Background Block-sequential regularized expectation maximization (BSREM), commercially Q. Clear (GE Healthcare, Milwaukee, WI, USA), is a reconstruction algorithm that allows for a fully convergent iterative reconstruction leading to higher image contrast compared to conventional reconstruction algorithms, while also limiting noise. The noise penalization factor β controls the trade-off between noise level and resolution and can be adjusted by the user. The aim was to ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
35
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 39 publications
(37 citation statements)
references
References 20 publications
2
35
0
Order By: Relevance
“…The authors reported superior SNR at matched noise in a liver VOI with Q.Clear (β of 133 to 533) compared to PSF+TOF (3 it, 16 ss, 5.0 mm filter), and clinical whole-body FDG-PET data with β of 267 to 533 achieved the highest score in subjective image quality [8]. Trägårdh et al found a β of 500 to 600 to be optimal for whole-body FDG-PET with the 4-ring detector GE Discovery MI if the product "AT" of injected activity per kilogram and acquisition time per bed position was 6 (i.e., 4 MBq/kg and 1.5 min acquisition) [18]. The same group recommended a β of 400 to 550 for 18F-fluorocholine PET if "AT" was 6 [19].…”
Section: Discussionmentioning
confidence: 99%
“…The authors reported superior SNR at matched noise in a liver VOI with Q.Clear (β of 133 to 533) compared to PSF+TOF (3 it, 16 ss, 5.0 mm filter), and clinical whole-body FDG-PET data with β of 267 to 533 achieved the highest score in subjective image quality [8]. Trägårdh et al found a β of 500 to 600 to be optimal for whole-body FDG-PET with the 4-ring detector GE Discovery MI if the product "AT" of injected activity per kilogram and acquisition time per bed position was 6 (i.e., 4 MBq/kg and 1.5 min acquisition) [18]. The same group recommended a β of 400 to 550 for 18F-fluorocholine PET if "AT" was 6 [19].…”
Section: Discussionmentioning
confidence: 99%
“…The commercially available block-sequential regularized expectation maximization (BSREM) (Q.Clear; GE Healthcare) reconstruction method implements regularization by a relative difference penalty ( De Pierro and Yamagishi, 2001 , Nuyts et al, 2002 , Ross, 2014 ), and allows the user to adjust the strength of the activity-dependent smoothing. Studies addressing whole body [ 18 F]FDG on various PET/CT scanners have shown for BSREM to reduce image noise without impeding the tumor detectability, or vice versa, to improve tumor detectability at similar noise levels as ordered-subsets expectation maximization (OSEM) ( Teoh et al, 2016 , Sah et al, 2017 , Lindström et al, 2018 , Trägårdh et al, 2019 , Bjöersdorff et al, 2019 ). Other studies have also shown the need to adjust the setting of β depending on the tracer and application being used ( Lindström et al, 2019 , Lindström et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Under these conditions, they found higher SUV and tumour-to-background ratios for BSREM compared to OSEM, especially for small and highly avid lesions. Optimization of BSREM has also been published on other radiopharmaceuticals, which include [ 18 F]fluorodeoxyglucose [17][18][19][20], [ 18 F]fluorocholine [13], and [ 18 F]fluciclovine [21], with different optimal β values and acquisition times. The differences depend on different bio-kinetics of the radiopharmaceutical, and different amounts of administered activity, which cause different amounts of signal in the images.…”
Section: Discussionmentioning
confidence: 99%